Metal-agglomeration-suppressed growth of MoS2 and MoSe2 films with small sulfur and selenium molecules for high mobility field effect transistor applications. Issue 32 (31st July 2018) - Jung, Kwang Hoon; Yun, Sun Jin; Choi, Yongsuk; Cho, Jeong Ho; Lim, Jung Wook; Chai, Hyun-Jun; Cho, Dae-Hyung; Chung, Yong-Duck; Kim, Gayoung
Abstract : This work reports an innovative method for achieving high quality MoS2 and MoSe2 films uniformly on large-area wafers at growth temperatures of 600 °C or lower. Abstract : This work reports a breakthrough technique for achieving high quality and uniform molybdenum dichalcogenide (MoX2 where X = S, Se) films on large-area wafers via metal-agglomeration-suppressed growth (MASG) with small chalcogen (X-) molecules at growth temperatures ( T G ) of 600 °C or lower. In order to grow MoS2 films suitable for field effect transistors (FETs), S-molecules should be pre-deposited on Mo films at 60 °C prior to heating the substrate up to T G . The pre-deposited S-molecules successfully suppressed the agglomeration of Mo during sulfurization and prevented the formation of protruding islands in the resultant sulfide films. The small X-molecules supplied from a thermal cracker reacted with Mo-precursor film to form MoX2 . The film quality strongly depends on the temperatures of cracking and reservoir zones, as well as T G . The MoS2 film grown at 570 °C showed a thickness variation of less than 3.3% on a 6 inch-wafer. The mobility and on/off current ratio of 6.1 nm-MoS2 FET at T G = 570 °C were 59.8 cm 2 V −1 s −1 and 10 5, respectively. The most significant advantages of the MASG method proposed in this work are its expandability to various metal dichalcogenides on larger substrates as well as a lower T G enabled by using reactive small molecules supplied from a cracker, for which temperature is independently controlled.